Herramienta de toma de decisiones para la implementación nacional del sistema multilateral de acceso y distribución de beneficios del Tratado Internacional sobre los Recursos Fitogenéticos - Joint Capacity Building Programme (Bioversity International, 2018)
This decision making tool is designed to assist national policy makers and other stakeholders to identify appropriate measures to implement the Plant Treaty’s multilateral system of access and benefit-sharing in their countries. It is the product of eight years of experience working with partners in numerous countries developing national policies under the overall framework of the FAO/Bioversity International/ITPGRFA Secretariat Joint Capacity Building Programme for Developing Countries on Implementation of the ITPGRFA and its Multilateral System of Access and Benefit-sharing. The decision-making tool is divided into the following eleven sections corresponding to issues that national-level policy actors need to address: 1. Who is responsible for promoting and coordinating national implementation? 2. What is facilitated access to PGRFA under the multilateral system and who has the right to facilitated access? 3. Who may authorize access to PGRFA under the multilateral system? 4. What processes and criteria should be followed to consider requests for PGRFA included in the multilateral system? 5. How to deal with requests for purposes that are (or may be) beyond the scope of the multilateral system? 6. What PGRFA are automatically included in the multilateral system? 7. How to encourage voluntary inclusions by natural and legal persons? 8. How to ensure legal space for the implementation of the multilateral system? 9. How to address benefit-sharing? 10. How to deal with reporting obligations regarding transfers and sales? 11. Who monitors the use of PGRFA under the multilateral system and enforces the multilateral system’s terms and conditions?